Juridical Review of Delays and Loss of Goods Users of PT. Pos Indonesia Services - Nurdin, Boy; Muntaha, Sugeng (Jurnal Indonesia Sosial Sains, 2023)
The objective of this research is to scrutinize the responsibilities and privileges of both the consumer, who is the sender of the goods and PT. Pos Indonesia, as specified in UUPK Articles 4 and 5, which establish consumer rights and obligations, as well as UUPK Articles 6 and 7, which delineate the rights and obligations of commercial actors. The research used is normative legal research using field data as a complement. Normative legal research methods are also called doctrinal legal research. Rights and Obligations of PT. Pos Indonesia and Consumer Service Users are guaranteed in Law Number 8 of 1999 concerning Consumer Protection Articles 4 to Article 7 and Law Number 38 of 2009 concerning PT. Pos Indonesia in Article 29 to Article 31 paragraph (1). The Post Office is responsible for the shipment from the time it is received until it is handed over to the intended recipient. Postal Law Number 38 of 2009 Article 31 concerning Postal Obligations in Compensation and Article 19 concerning the obligations of business actors both outlined how postal parties must compensate for losses for delays or damage to goods. Compensation, if deemed necessary, will be replaced within six working days of receiving the claim. The rules that apply to claims for compensation are in the Decision of the Directors of PT. Pos Indonesia (Persero) Regarding the First Amendment on the Decision of the Directors of PT. Pos Indonesia (Persero) Number KD.112/DIR5/1118 Concerning Compensation Guarantee for Courier Delivery and Domestic Logistics if there is a discrepancy between the goods sent and those received, then according to this decision, consumers can claim compensation from the Post Office